Lepidocyrtus mariani sp. n., a new springtail species - Traser, Gy. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2008)
Lepidocyrtus mariani sp. n. is described from Hungary. The new species is close to Lepidocyrtus flexicollis Gisin, 1965 sensu Mateos, 2008, but differs in the interocular chaetotaxy by the presence of the seta “q” and in the high number of the setae on the manubrial plate: 10–18 in L. flexicollis, about 30 in the new species